Phonological Features of Contemporary Spoken Binukid - Hermocilla-Borres, Teresita (Journal of Modern Languages, 2018)
This paper attempts to describe the phonological features of Binukid language, which is one of the indigenous languages spoken by the lumads, particularly the Umajamnen tribe, in Bukidnon, Southern Philippines. The study anchored its framework of analysis from the International Phonetic Alphabet (IPA) in Ladefoged (2012) for the phonetic notations and standardized representations. Proper research protocols were observed such as the seeking of consent from the National Commission on Indigenous Peoples (NCIP) in the Province, the tribal informed consent, and the conduct of the traditional pamuhat ritual. Informants were properly identified and qualified based on language use in the home domain. Results revealed that Binukid has 16 consonants: the /b/, /k/, /d/, /g/, /h/, /j/, /l/, /m/, /n/, / ®_ /, /p/, /r/, /s/, /t/, /w/, and /y/. It has five vowels: the /a/, the pepet /e/, /i/, /o/, and /u/; and finally, it has five diphthongs: the high-front /ei/, the front central /au/, the low central back /ai/, the central /ƒÓi/ and the back central /ou/. Significant findings include the following: identification of the pepet /e/, the alveo-palatal affricate /j/; and the presence of the five dipthongs: the /ƒÓi/, /au/, /ai/, /ƒªi/, and /ow/. These findings were not mentioned in the early descriptions of related Binukid phonology in the studies of Atherton (1953, 1963); Post (1965, 1968), and Post & Gardner (1965). Finally, the study found interchangeability of some vowels and consonants among the elderly in the community, and the preponderance of the /a/, the peppet /e/, and the /j/ in the corpus.